THE EFFECT OF HUMAN RESOURCE MANAGEMENT PRACTICES, UNIQUE PROPRIETARY INPUTS AND PROCESS AND ORGANIZATIONAL CULTURE ON BUSINESS SCHOOL PERFORMANCE: A CASE STUDY ON MANAGEMENT AND INSTRUCTORS OF THAI BUSINESS SCHOOLS - ปานมณี, พงศธร; สุพิชญางกูร, สุรัติ (RMUTT Global Business and Economics Review, 2016)
This study aimed to investigate the factors affecting Thai business school performance. Data were collected from a sample of 466 faculty members of Thai business schools, by using the structural equation modeling (SEM). In order to obtain the good fit model, the AMOS (analysis of moment structures) program was employed to construct the measurement models in confirming the latent variable of the business school performance model through the confirmatory factor analysis. The research findings indicatd that the measurement models were fit models, the exploratory factor analysis and regression analysis were utilized to specify the factors affect of business schools performance. The results showed that the most significant factor that affect Thai Business school performance was organizational culture and all factors (human resource management practices, unique proprietary input and process, organizational culture affected affect to business school performance. The R2 of the model is 0.376. This mean that explanatory variables of this model were able to explain and predict business school performance by 37.6%. These findings will contribute to university executive officers, faculty members and government agencies for business school management